(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article highlights the influence of baroque aesthetics on Cornelius’s drama. The author’s numerous plays preserves baroque traditions on the level of the plot, dramatic emotions and the concept of characters. The usage of theatrical baroque devices has been researched as a means of reflecting variability and dynamics of life, contradictions and antinomies of the epoch.